Akuntansi, Budaya, dan Korupsi: Sebuah Studi antar Negara - Ahmad Dzakwan; Syarifuddin Syarifuddin; Amiruddin Amiruddin (Al-Buhuts, 2023)
The purpose of this study is to determine and analyze the influence of accounting and culture on the level of corruption in countries. The study uses the adoption status of international accounting standards as a proxy for the accounting variable, Hofstede's cultural dimensions for culture variable, and measures a country's level of corruption using the Corruption Perception Index. The research data are obtained from adoption status of international accounting standards published by IFAC and IASB, Hofstede's cultural dimensions published by Hofstede Insights, and Corruption Perceptions Index published by Transparency International for the observation period of 2022-2023. The study employs multiple linear regression analysis of the data with a sample size of 83 countries obtained using purposive sampling. The results show that a country can reduce its level of corruption by adopting international public sector accounting standards and international financial reporting standards. The study also indicates that a country's level of corruption increases if the country is characterized by high power distance, collectivism, masculinity, high uncertainty avoidance, long-term orientation, and restraint cultural dimensions. Meanwhile, adoption of international education standards, international standards on auditing, and code of ethics for professional accountants has no significant influence on reducing a country's level of corruption